Pemanfaatan Aplikasi Tiktok Sebagai Media Pembelajaran Musik di SMAN 1 Muara Enim, Sumatera Selatan - Dian Herdiati; Dhika Dwi Atmaji; Raden Mas Aditya Andriyanto; Dani Nur Saputra (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
The ongoing pandemic conditions until now, causing the learning process to be done online. Online learning seems boring because the online learning methods and media that are applied are less creative and varied. Teachers' incompetence in using technology is one of the causes of boring learning, so schools and teachers are trying to find the right method or media to make learning more interesting. The purpose of this study is to describe the TikTok application as music learning media from SMAN 1 Muara Enim, South of Sumatra. The research method used was a descriptive qualitative research method. This research was conducted in Perumahan Bumi Eraska Blok E7 no 12. The researcher got the data from observation of the learning outcomes of students and teacher of SMAN 1 Muara Enim South Sumatra, through Youtube and the TikTok application. The time of this research was conducted from March to June. Data collected were the result of interviews, literature, observation, and documentation. The result of this research indicates that the TikTok application can be used as a music learning medium. In utilizing the TikTok application there  must be appropriate steps and methods to achieve learning objectives. there are positive effects in the use of the TikTok application at SMAN 1 Muara Enim, namely can make students get more confidence in the music subject, familiarizing students with the use of technology 4.0 especially in the music subject, increasing student interaction during distance learning, making it easier for teachers and students with its features to make music learning videos, make students more interactive, and as a promotional tool for the school.